2020
DOI: 10.1037/edu0000399
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations of classroom goal structures to students’ motivation and learning outcomes in health education.

Abstract: Little attention has been paid to goal structures in health education, despite their well-established roles in motivation and learning. The primary goal of this study was to examine the longitudinal relations of classroom goal structures to high school students’ (N = 636) motivation and learning outcomes in health education. We incorporated two aspects of motivation: self-efficacy for negotiating condom use and task values for learning new information about HIV and pregnancy prevention. Results revealed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 98 publications
(184 reference statements)
2
8
0
Order By: Relevance
“…This result implies that the more students are motivated to learn, the higher their chances of maintaining acceptable learning outcomes in secondary schools. The result of this study strengthens the finding of researchers that also documented that students’ motivation relates positively to their academic achievement ( Momany et al, 2015 ) and learning outcomes ( Georgiou and Kyza, 2018 ; Won et al, 2020 ; Cho et al, 2021 ; Howard et al, 2021 ). Regarding the strength of the relationship, the current study found a weak predictive relationship between motivation and students’ learning outcomes generally and across the three domains.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result implies that the more students are motivated to learn, the higher their chances of maintaining acceptable learning outcomes in secondary schools. The result of this study strengthens the finding of researchers that also documented that students’ motivation relates positively to their academic achievement ( Momany et al, 2015 ) and learning outcomes ( Georgiou and Kyza, 2018 ; Won et al, 2020 ; Cho et al, 2021 ; Howard et al, 2021 ). Regarding the strength of the relationship, the current study found a weak predictive relationship between motivation and students’ learning outcomes generally and across the three domains.…”
Section: Discussionsupporting
confidence: 88%
“…However, Marsela (2017) found that student enthusiasm to learn had a modest impact on students’ ability to read and comprehend. Studies have documented that students’ motivation relates positively to their academic achievement ( Momany et al, 2015 ) and learning outcomes ( Georgiou and Kyza, 2018 ; Won et al, 2020 ; Cho et al, 2021 ; Howard et al, 2021 ). More specifically, it was discovered that students’ self-test scores for extrinsic motivation rise when their academic success rises and vice versa ( Sivrikaya, 2019 ; Wagbara and Furo, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another implication of this study is that the impact of perfectionism among teachers is far‐reaching, potentially affecting student learning. The results of the study showed that teachers’ perfectionistic concerns demonstrated a strong influence on teaching practices (i.e., inclination [or lack thereof] to create a particular type of classroom goal structure), which has a direct effect on students’ learning (Linnenbrink, 2005; Won et al, 2019). Though there was a significant negative relationship between teachers’ concern over mistakes and the provision of mastery goal structure, no significant relationship was found between teachers’ concern over mistakes and their own mastery goals for teaching.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done through various classroom rules and procedures (e.g., grading and grouping), as well as informal interactions with students (e.g., praising the best‐performing students vs. praising the student who made a great personal improvement). This is referred to as a classroom goal structure (Meece, Anderman, & Anderman, 2006; Wolters, 2004; Won, Anderman, & Zimmerman, 2019). Mastery goal structure refers to a classroom environment where personal growth, skill mastery, value of effort, and learning for its own sake are valued.…”
Section: Creation Of Classroom Goal Structure and Perfectionismmentioning
confidence: 99%
“…A review of the available literature showed that organizational factors have a significant impact on the quality of learning outcomes in elementary education and are a framework for sustainability in elementary education. This research recognizes the potential of factors such as managerial skills of principals, school managers, teaching resources, infrastructure, and curriculum management, which highlights Wahyono (2015), then prior knowledge and motivation of students (Lin et al, 2016;Won et al, 2020), and the quality of the teaching process (Asfani et al, 2016), to achieve a certain level of impact on the quality of learning outcomes. While many studies deal with the influence of individual factors on various aspects related to higher education (Haapakorpi, 2011;Ďurišová et al, 2015;Cruickshank, 2017), the influence of these factors as a set should be investigated in more detail in relation to the quality of initial knowledge in elementary education.…”
Section: Introductionmentioning
confidence: 99%